Bringing space back in: organizing the generative building - Kornberger, Martin; Clegg, Stewart R. (2004)
In this article, we reflect on architecture and management and organization theory, in terms of their mutual implications. We focus especially on a tacit implication in mainstream organization theory, which has an architectural genesis. In the past, management has been largely undergirded by a Cartesian rationality, one seen most clearly in the argument that structure follows strategy. Architecturally, this Cartesianism is present in the injunction that form follows function. Criticizing this point of view, we argue that organizations should be thought of as material, spatial ensembles - not just cognitive abstractions writ large. Linking space and organization in this way, we reflect on the power that every spatial organization necessarily implies, both in negative and positive terms. After examining existing approaches to this issue, we discuss some positive power implications for management. We introduce the concept of the generative building that, instead of being a merely passive container for actions happening in it, contributes positively towards an organization's capacities. We conclude with a reflection on the impact of the generative building on management and processes of organizing. - Reproduced.
Keywords: Buildings; Organizations; Space; Architecture